Roles of lncRNAs Mediating Wnt/β-Catenin Signaling in HCC - Xu, Yating; Yu, Xiao; Sun, Zongzong; He, Yuting; Guo, Wenzhi (Frontiers in Oncology, 2022)
Hepatocellular carcinoma (HCC) is considered the second most deadly cancer worldwide. Due to the absence of early diagnostic markers and effective therapeutic approaches, distant metastasis and increasing recurrence rates are major difficulties in the clinical treatment of HCC. Further understanding of its pathogenesis has become an urgent goal in HCC research. Recently, abnormal expression of long noncoding RNAs (lncRNAs) was identified as a vital regulator involved in the initiation and development of HCC. Activation of the Wnt/β-catenin pathway has been reported to obviously impact cell proliferation, invasion, and migration of HCC. This article reviews specific interactions, significant mechanisms and molecules related to HCC initiation and progression to provide promising strategies for treatment.